Tunable Bragg polaritons and nonlinear emission from a hybrid metal-unfolded ZnSe-based microcavity - SK. Shaid-Ur Rahman (Nature Portfolio, 2017)
Abstract Strong light-matter interaction in Bragg structures possesses several advantages over conventional microcavity system. These structures provide an opportunity to incorporate a large number of quantum wells without increasing the mode volume. Further, it is expected that the strong coupling could occur over the entire thickness of the Bragg structure, and the system offers an improved overlap between exciton wave function and light mode. However, advanced experiments in Bragg structures require a precise control and manipulation of quantum states of Bragg polaritons. Here, we propose and experimentally demonstrate novel methods for the modulation of Bragg polariton eigenstates. The modulation will be shown to even exceed 10 meV if the thickness of the top layer of the ZnSe-based Bragg structure is changed or if a thin silver layer is deposited on top of the structure. The Q value of the Bragg mode will be enhanced by a factor of 2.3 for a 30 nm silver layer. In addition, we report on the observation of nonlinear emission of the lower Bragg polariton mode in the hybrid structure being achieved when excitation dependent measurements are performed. Our results open the door to create a confined Bragg polariton system similar to conventional microcavities.